2020
DOI: 10.1007/s11136-020-02418-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in people with dementia living in nursing homes: validation of an eight-item version of the QUALIDEM for intensive longitudinal assessment

Abstract: Purpose Our aim was to examine whether quality of life which was repeatedly assessed over time is related with the comprehensive assessment of quality of life (QoL) and thereby to validate a brief QoL assessment. Method This longitudinal study used a comprehensive assessment of quality of life at baseline (QUALIDEM; 37 items) to validate an eight-item version of QUALIDEM to assess momentary quality of life which was repeatedly administered using a tablet device after baseline. In all, 150 people with dementia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…An eight-item version of the QUALIDEM was used to conduct EMA of momentary quality of life. Psychometric properties of the QUALIDEM short version have been published elsewhere (Junge et al, 2020). Neuropsychiatric symptoms were measured with the informant-based NPI-NH questionnaire (Cummings et al, 1994).…”
Section: Measurementsmentioning
confidence: 99%
“…An eight-item version of the QUALIDEM was used to conduct EMA of momentary quality of life. Psychometric properties of the QUALIDEM short version have been published elsewhere (Junge et al, 2020). Neuropsychiatric symptoms were measured with the informant-based NPI-NH questionnaire (Cummings et al, 1994).…”
Section: Measurementsmentioning
confidence: 99%
“…The scale demonstrated excellent reliability among activity therapists as well as family members and nursing assistants and good validity [20]. EMA has thus been used to monitor daily life behaviors and well-being in people with dementia, and these studies have demonstrated the validity of informant ratings and the ability to capture individual differences over time [20][21][22][23]. However, no EMA depression screening tools have been developed for people with advanced dementia.…”
Section: Ecological Momentary Assessmentmentioning
confidence: 99%
“…Ratings of the QUALIDEM short version were associated with ratings on the original QUALIDEM scale and showed good internal consistency with Cronbach's α with values ranging from .88 to .93 across sessions. Additional psychometric properties of the QUALIDEM short version have been published elsewhere (54).…”
Section: Ecological Momentary Assessments Of Quality Of Lifementioning
confidence: 99%